Remote working, digital skiil and knowledge acquisition on personnel performance in program kota tanpa kumuh (Kotaku) in West Sumatra - Hanafiah; Hafiz Rahman; Hendra Lukito (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of remote working, digital skills and knowledge acquisition on personnel performance in program Kota tanpa Kumuh (Kotaku) in West Sumatra, the population in this study were all personnel of the Kotaku Program in West Sumatera with a sample of 89 respondents. Data obtained by conducting a questionnaire, then processed and tested using SmartPLS.From the research conducted, it is known that based on the results of hypothesis testing, it is known that remote working, digital skills and knowledge acquisition have a significant effect on the performance of personnel in the Kota tanpa Kumuh (Kotaku) program in West Sumatra.